Proteins implicated in the increase of adhesivity induced by suberoylanilide hydroxamic acid in leukemic cells - Grebeňová, D; Röselová, P; Pluskalová, M; Halada, P; Rösel, D; Suttnar, J; Brodská, B; Otevřelová, P; Kuželová, K (Journal of proteomics, 2012)
We have previously shown that suberoylanilide hydroxamic acid (SAHA) treatment increases the adhesivity of leukemic cells to fibronectin at clinically relevant concentrations. Now, we present the results of the proteomic analysis of SAHA effects on leukemic cell lines using 2-DE and ProteomLab PF2D system. Histone acetylation at all studied acetylation sites reached the maximal level after 5 to 10 h of SAHA treatment. No difference in histone acetylation between subtoxic and toxic SAHA doses was observed. SAHA treatment induced cofilin phosphorylation at Ser3, an increase in vimentin and paxillin expression and a decrease in stathmin expression as confirmed by western-blotting and immunofluorescence microscopy. The interaction of cofilin with 14-3-3 epsilon was documented using both Duolink system and coimmunoprecipitation. However, this interaction was independent of cofilin Ser3 phosphorylation and the amount of 14-3-3-ε-bound cofilin did not rise following SAHA treatment. SAHA-induced increase in the cell adhesivity was associated with an increase in PAK phosphorylation in CML-T1 cells and was abrogated by simultaneous treatment with IPA-3, a PAK inhibitor. The effects of SAHA on JURL-MK1 cells were similar to those of other histone deacetylase inhibitors, tubastatin A and sodium butyrate. The proteome analysis also revealed several potential non-histone targets of histone deacetylases.
Keywords: Neoplasm Proteins; Cell Adhesion; K562 Cells; vorinostat; nádorové proteiny; Phosphorylation; Time Factors; Antineoplastic Agents; buňky K562; Proteome; protinádorové látky; Humans; kyseliny hydroxamové; časové faktory; acetylace; buněčná adheze; fosforylace; proteom; HL-60 buňky; Vorinostat; Acetylation; leukemie; Leukemia; lidé; HL-60 Cells; Hydroxamic Acids